2022
DOI: 10.3390/curroncol29050242
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment-Free Single-Cell Detection and Morphogenomic Profiling of Myeloma Patient Samples to Delineate Circulating Rare Plasma Cell Clones

Abstract: Multiple myeloma is an incurable malignancy that initiates from a bone marrow resident clonal plasma cell and acquires successive mutational changes and genomic alterations, eventually resulting in tumor burden accumulation and end-organ damage. It has been recently recognized that myeloma secondary genomic events result in extensive sub-clonal heterogeneity both in localized bone marrow areas and circulating peripheral blood plasma cells. Rare genomic subclones, including myeloma initiating cells, could be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…The biomarker-based classified groups represented candidate PCs, committed clonotypic B cells, and plasmablasts ( Figure 3 A). Quantification of the different circulating rare cell groups across patients showed that CD138+ cells were more abundant in neoplastic myeloma and not in NDs, with a higher proportion being found in NDMM than in precursor states (SMM and MGUS) ( Figure 3 B–D), consistent with our prior observations [ 19 , 20 ]. BCMA+ cells were detected in all samples, including NDs, confirming that the expression of BCMA in early B cells, although suggested to be low, is detectable in our assay.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The biomarker-based classified groups represented candidate PCs, committed clonotypic B cells, and plasmablasts ( Figure 3 A). Quantification of the different circulating rare cell groups across patients showed that CD138+ cells were more abundant in neoplastic myeloma and not in NDs, with a higher proportion being found in NDMM than in precursor states (SMM and MGUS) ( Figure 3 B–D), consistent with our prior observations [ 19 , 20 ]. BCMA+ cells were detected in all samples, including NDs, confirming that the expression of BCMA in early B cells, although suggested to be low, is detectable in our assay.…”
Section: Resultssupporting
confidence: 91%
“…Technical validation for CD138, CD45, and DAPI cells in HDSCAs has been previously reported [ 19 , 20 ]. In titration experiments with U266, MM.1S, and control Jurkat cells, BCMA expression was consistently higher in U266 and MM.1S across all concentration conditions, while no BCMA expression was detected in control Jurkat cells, as expected ( Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a different study, researchers used an enrichment-free four-plex immunofluorescence technique and single-cell DNA sequencing for identification and genomic classification of plasma cells to distinguish normal and malignant plasma cells in blood and BM aspirates from patients with newly diagnosed myeloma and monoclonal gammopathy of undetermined significance (MGUS) [ 33 ]. The results confirmed that peripheral blood plasma cells presented the same genomic modifications that were present in BM plasma cells.…”
Section: Liquid Biopsy and Circulating Tumour Cellsmentioning
confidence: 99%